Chronic glomerulonephritis associated with hepatosplenic schistosomiasis mansoni - Ramos, Eduardo Antonio Gonçalves; Andrade, Zilton A. (Revista do Instituto de Medicina Tropical de São Paulo, 1987)
In a series of 36 cases of renal disease associated with hepatosplenic schistosomiasis the following morphologic types of glomerulonephritis were found: mesangio-capillary (33.2%), mesangial proliferative (25.0%), focal glomerular sclerosis (16.7%) and sclerosing glomerulonephritis (8.3%). No significant statistical differences were found when these results were compared with those from 36 cases of glomerulonephritis not associated with hepatosplenic disease. On the other hand, endocapillary glomerulonephritis was found to be predominant in the latter group of cases. These results did not substantiate the assumption that mesangio-capillary glomerulonephritis is specifically related to hepatosplenic schistosomiais. However, if the types of glomerulonephritis that predominantly involve the me-sangium are considered together, they are significantly associated with hepatosplenic schistosomiasis. Mesangial involvement is known to occur in other parasitic diseases and that may be related to a common immunopathogenesis.